Pengaruh Penggunaan Media Pembelajaran Mind Mapping Islami Terhadap Kemampuan Siswa Berpikir Kritis - Sulistyo Wati, Endang; Nurdyansyah (PAI RAFAH, 2025)
This research was conducted using teacher notes as a guide in providing material using learning media. There are still many teachers who rarely use learning media when delivering material or in the learning process. This learning media is very important for students because they consider that learning is more fun and not scary. This study aims to analyze the effect of using mind mapping media in teaching general knowledge by using before and after tests. Data collection techniques used questionnaires and observation. Data analysis used questions totaling 15 questions. This study obtained the results that from all indicators that have been exceeded, it was identified that there was a significant increase in influence of 0.002 related to before and after utilizing mind mapping learning media. The application of mind mapping media by the fifth grade teacher of MI MA'ARIF KEDUNGBOTO is able to improve students' critical thinking